An intensification of surface Earth’s energy imbalance since the late 20th century - Xuqian Li; Qingxiang Li; Martin Wild; Phil Jones (Communications Earth & Environment)
Abstract Tracking the energy balance of the Earth system is a key method for studying the contribution of human activities to climate change. However, accurately estimating the surface energy balance has long been a challenge, primarily due to uncertainties that dwarf the energy flux changes induced and a lack of precise observational data at the surface. We have employed the Bayesian Model Averaging (BMA) method, integrating it with recent developments in surface solar radiation observational data, to refine the ensemble of CMIP6 model outputs. This has resulted in an enhanced estimation of Surface Earth System Energy Imbalance (EEI) changes since the late 19th century. Our findings show that CMIP6 model outputs, constrained by this observational data, reflect changes in energy imbalance consistent with observations in Ocean Heat Content (OHC), offering a narrower uncertainty range at the 95% confidence level than previous estimates. Observing the EEI series, dominated by changes due to external forcing, we note a relative stability (0.22 Wm−2) over the past half-century, but with a intensification (reaching 0.80 Wm−2) in the mid to late 1990s, indicating an escalation in the adverse impacts of global warming and climate change, which provides another independent confirmation of what recent studies have shown.